Star Darlings collection. Volume 3 - Zappa, Shana Muldoon; Zappa, Ahmet; Rose, Zelda (Disney Press, 2016)
"Disturbing things continue to happen on Starland every day, beginning when Piper's Star Kindness Day compliment poems for her friends turn into cruel insults. As the Star Darlings unravel clues, they begin to suspect that one of their own is behind the trouble...and that it might be Lady Stella. Piper enjoys her time working in a diner on Wishworld...but is she being a little too laid-back about her mission? When Astra's turn comes, her overconfident nature leads her to incorrect conclusions about her gymnast Wisher's true wish. Tessa's mission brings her to an animals shelter, but when a terrible storm hits, she runs into problems"--Page [4] cover.